2022
DOI: 10.1002/ggn2.202100060
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Cell Transcriptome Identifies Drug‐Resistance Signature and Immunosuppressive Microenvironment in Metastatic Small Cell Lung Cancer

Abstract: Small cell lung cancer (SCLC) is a deadly neuroendocrine malignancy with high metastasis. However, the heterogeneity of metastatic SCLC at the single‐cell level remains elusive. The single‐cell transcriptome of a total of 24 081 cells in metastatic lymph node samples from seven SCLC patients via endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) is examined. Genomic alterations are also examined by whole exome sequencing (WES) and the immune infiltration between SCLC and non‐SCLC (NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…FZD8, a constituent of the frizzled (FZD) protein family, functions as a receptor for WNT ligands. Prior studies indicated that FZD8 is overexpressed in diverse tumours, resulting in bone metastasis and resistance to treatment by activating the canonical Wnt/β‐catenin pathway 51,72,73 . In the current study, we identified FZD8 as a critical downstream gene activated by YY1 via promoter binding.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…FZD8, a constituent of the frizzled (FZD) protein family, functions as a receptor for WNT ligands. Prior studies indicated that FZD8 is overexpressed in diverse tumours, resulting in bone metastasis and resistance to treatment by activating the canonical Wnt/β‐catenin pathway 51,72,73 . In the current study, we identified FZD8 as a critical downstream gene activated by YY1 via promoter binding.…”
Section: Discussionmentioning
confidence: 56%
“…Prior studies indicated that FZD8 is overexpressed in diverse tumours, resulting in bone metastasis and resistance to treatment by activating the canonical Wnt/β-catenin pathway. 51,72,73 In the current study, we identified FZD8 as a critical downstream gene activated by YY1 via promoter binding. An enhanced binding effect of FZD8 to Wnt9A after ADT was observed in PCa cell membranes based on IF assay results, thus contributing to PCa cell plasticity by activating a non-canonical Wnt pathway (FZD8/FYN/STAT3).…”
Section: Discussionmentioning
confidence: 81%
“…Recently, some groups including us have investigated the single-cell transcriptome of primary and metastatic SCLC tissues. 55,61,62 Although they have been reported in only a few studies on NSCLC, 63,64 single-cell multiomics technologies 65 will uncover genome-wide methylation/hydroxymethylation in SCLC, as well as other useful information, such as transcription, histone modification and chromatin accessibility. Second, circulating cell-free DNA (cfDNA) provides a good resource for liquid biopsy by minimally invasive method because of its stability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DNA methylation should be revealed at single‐cell resolution as TME comprises a complex of different cell types. Recently, some groups including us have investigated the single‐cell transcriptome of primary and metastatic SCLC tissues 55,61,62 . Although they have been reported in only a few studies on NSCLC, 63,64 single‐cell multiomics technologies 65 will uncover genome‐wide methylation/hydroxymethylation in SCLC, as well as other useful information, such as transcription, histone modification and chromatin accessibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation